Towards an international standard: the ISO/DIS 18504 Sustainable remediation - Nathanail, C. Paul; BAkker, Laurent M.M.; Bardos, Paul; Furukawa, Yasuhide; Nardella, Alessandro; Smith, Garry; Smith, Jonathan; Goestsche, Gabriele (Wiley, 2017)
Sustainable remediation is the elimination and/or control of unacceptable risks in a safe and timely manner while optimizing the environmental, social, and economic value of the work. Forthcoming International Organization for Standardization (ISO) Standard on Sustainable remediation will allow countries without the capacity to develop their own guidance to benefit from work done over the past decade by various groups around the world. The ISO standard has progressed through the committee draft (ISO/CD 18504) and draft international standard (ISO/DIS 18504) stages. The risk-based approach to managing the legacy of historically contaminated soil and groundwater has been incorporated into policy, legislation, and practice around the world. It helps determine the need for remediation and the end point of such remediation. Remediation begins with an options appraisal that short lists strategies that could deliver the required reduction in risk. A remediation strategy comprises one or more remediation technologies that will deliver the safe and timely elimination and/or control of unacceptable risks. The ISO standard will help assessors identify the most sustainable among the shortlisted, valid alternative remediation strategies. Practitioners presenting case studies claiming to constitute sustainable remediation should now report how they have aligned their work with the new standard. Indicators are used to compare alternative remediation strategies. The simplest metric that allows a characteristic to act as an indicator should be chosen. Weightings indicators can become a contested exercise and should only be undertaken where there is a clear desire for it by stakeholders and a clear need for it in identifying a preferred strategy. The simplest means of ranking alternative remediation strategies should be adopted.